ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN MEDICAL PRACTICE - Mintser, O. P.; Romanov, V. O.; Galelyuka, I. B.; Voronenko, O. V. (Medical Informatics and Engineering, 2020)
Background. The integrated digitalization of medicine, the use of the Internet of Intelligent Things, and the networks of medical wireless sensors offers ample opportunities to remotely support the appropriate quality of life of chronically ill patients, the elderly, and athletes and professionals with heavy physical or mental workloads. Materials and methods. Results. The implementation of individual remote means of maintaining quality of life includes the following components: the creation of new and the use of existing miniature or microelectronic medical sensors that directly read medical parameters from the patient's body. Such sensors are designed to monitor body temperature, heart rate, respiration and blood pressure, read heart signals, determine skin moisture, record a fall or abrupt changes in the patient's position and other body parameters in real time, miniature interfaces for data acquisition, analog-to-digital conversion and data preprocessing of medical parameters received from medical sensors located on the patient's body, miniature data communication means to remote medical centers according to modern communication standards, automated and remote diagnostic tools with elements of artificial intelligence, remote-controlled injectors for input of medicines in case of critical condition of the patient. Conclusions. The current state and prospects for the development of these tools are discussed in the publication.